The dimension of biological change caused by autotriploidy: a meta-analysis with triploid crayfish Procambarus virginalis and its diploid parent Procambarus fallax - Vogt, Günter (Zoologischer Anzeiger, 2019)
The biological changes caused by autotriploidy are poorly studied in animals. To investigate this issue in depth, we compared genetics, morphology, life history, ecology and behaviour of the triploid marbled crayfish and its diploid parent, slough crayfish Procambarus fallax. We performed a meta-analysis of our data and literature data. Our COI based molecular tree, consisting of 27 species of Cambaridae, confirmed the close taxonomic relationship between marbled crayfish and P. fallax. Comparison of both crayfish revealed similarities in mitochondrial gene sequences, morphological characters, colouration, body proportions and behaviours. Considerable differences were recorded with respect to chromosome number in somatic cells, haploid genome size, DNA methylation level, body size, fecundity, longevity, population size structure, invasiveness, and the range of inhabited biomes. These differences have dimensions that are otherwise only observed between species supporting earlier proposed raising of marbled crayfish from P. fallax forma virginalis to a new species named Procambarus virginalis. Particularly noteworthy is the enhancement of the fitness traits that probably resulted from evolutionary changes in gene expression. These alterations and the transition from sexual reproduction to parthenogenesis are likely responsible for the increased invasiveness of marbled crayfish in tropical to cold-temperate biomes.